Addressing Child Marriage in India Through the Implementation of the Global Programme to End Child Marriage by UNFPA and UNICEF from 2016 to 2023 - Manurung, Bela Sartina; Rasyidah, Resa (Universitas Tribhuwana Tungga Dewi, 2025)
This research examines the implementation of the Global Programme to End Child Marriage initiated by the United Nations Population Fund and the United Nations Children's Fund in India during the 2016-2023 period. India, which previously had a high prevalence of child marriage practices, has shown a significant decrease and even led the global decline in child marriage prevalence over the last decade. The study applies the theory of International Organization and Implementation with a management approach as an analytical framework. The methodology employed is descriptive with qualitative data analysis techniques. Data collection relies on document analysis and official publications from relevant sources. The results reveal that the United Nations Population Fund and the United Nations Children's Fund implement the Global Programme through a management approach in three ways: monitoring, capacity building, and problem solving. Monitoring is carried out through data information systems and field visits, with adaptations made during the pandemic. Capacity building includes life skills enhancement, educational programs, and empowerment initiatives. Problem solving focuses on financial issues, research, education, and adjustments to pandemic challenges. This research provides in-depth insights into international organization interventions in addressing complex social issues at the national level.Â Penelitian ini mengkaji implementasi Global Programme to End Child Marriage yang diinisiasi oleh United Nations Population Fund dan United Nations Children's Fund di India selama periode 2016-2023. India, yang sebelumnya memiliki prevalensi tinggi dalam praktik pernikahan anak, telah menunjukkan penurunan signifikan bahkan memimpin dalam penurunan prevalensi pernikahan anak secara global dalam dekade terakhir. Studi ini mengaplikasikan teori International Organization and Implementation dengan management approach sebagai kerangka analitis. Metodologi yang digunakan adalah deskriptif dengan teknik analisis data kualitatif. Pengumpulan data mengandalkan analisis dokumen dan publikasi resmi dari sumber-sumber terkait. Hasil penelitian mengungkapkan bahwa United Nations Population Fund dan United Nations Children's Fund mengimplementasikan Program Global melalui management approach melalui tiga cara: monitoring, capacity building and problem solving. Monitoring dilaksanakan melalui sistem informasi data dan kunjungan lapangan, dengan adaptasi selama pandemi. Capacity building meliputi peningkatan keterampilan hidup, program pendidikan, dan inisiatif pemberdayaan. Problem solving berfokus pada isu-isu keuangan, penelitian, pendidikan, dan penyesuaian terhadap tantangan pandemi. Penelitian ini memberikan wawasan mendalam tentang intervensi organisasi internasional dalam mengatasi permasalahan sosial yang kompleks di tingkat nasional.